Neoliberalism, an element of influence in the public policies of organizations: The case of the Consejo Nacional de Ciencia y Tecnología in Mexico - Dimas, Thalia Ponce; González Cruz, Erik Geovany (Política. Revista de Ciencia Política, 2021)
The neoliberalism it’s an ideology in Latin America. In this paper taken the relation betwen the neoliberal thinking and the action in Consejo Nacional de Ciencia y Tecnologia in Mexico, described this phenomen in two diferent moments in Mexican politics. In the begining speaken about neoliberalism, mark out in the caractheristics and consequences. Then be described CONACYT and the their politic in the last goverment, in specific 2012-2018. At the last be described the proposed routes to this goverment (2018-2024). It concludes analising the ideologic elements externals like the neoliberalism, be taken to study the behavior in public organizations.